How Public Spending Can Help You Grow : An Empirical Analysis for Developing Countries - Moreno-Dodson, Blanca; Bayraktar, Nihal (World Bank, Washington, DC, 2012)
Although many studies indicate that both the level and composition of public spending are significant for economic growth, the results in the empirical literature are still mixed. This note is based on a paper of the same title (Bayraktar and Moreno-Dodson 2010) that compares a set of fast-growing developing countries to a mix of developing countries with different growth patterns. Considering the full government budget constraint, the empirical analysis shows that public spending, especially its 'core' components, contributes to economic growth only in countries that are capable of using funds for productive purposes. In addition, those countries must have an adequate economic policy environment with macroeconomic stability, openness, and private sector investments that are conducive to growth.